2021
DOI: 10.1108/s1058-749720210000029007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Governance Quality and Religiosity on Tax Evasion: Evidence from OECD Countries

Abstract: The study examines the effects of governance quality and religiosity on tax evasion (TE) in the OECD (Organisation for Economic Co-operation and Development) countries. Further, the study investigates which government qualities and religiosities affect TE significantly. Ordinary least squares has been used to analyze the data gathered from 36 OECD countries covering the period of 2002-2015 based on the latest data of TE. The results show the negative impact of governance quality and religiosity on TE; it impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…That being said, nontransparent government, inefficient policies and unfair regulations will compromise the government's legitimacy, erode trust and fuel TEVA (Rashid et al, 2021).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…That being said, nontransparent government, inefficient policies and unfair regulations will compromise the government's legitimacy, erode trust and fuel TEVA (Rashid et al, 2021).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Prior studies have investigated many factors that demotivate taxpayers from paying taxes (Abdixhiku et al, 2018; Alm, 2019; Alm et al, 2019; Epaphra, 2015; Nurunnabi, 2018; Rashid et al, 2021) and have identified either economic or non-economic factors of tax evasion (Alm et al, 2019; Epaphra, 2015; Nurunnabi, 2018). Some scholars consider corruption and crime as the major determinants of tax evasion (Alm et al, 2016).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The tax authority is the central body that collects the tax; its objective is to provide good administration (good governance) in taxation. Finally, individuals’ tax-paying behavior will be determined by their interaction with the state and tax authorities and their culture and ethical beliefs (Rashid et al, 2021). Therefore, successful tax planning must go beyond the narrow measures of the government to provide laws and benefits to the taxpayers, and it also includes the interactive force of all three parties involved.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Records routinely offer commentary on the efficiency and profitability of operations. Sawyer et al (2021) assert that accurate reporting of revenue and expenses in corporate tax filings results from maintaining accurate records. For businesses to comply with tax regulations, keeping correct records is essential.…”
Section: Individual Motivators Of Tax Compliancementioning
confidence: 99%